Case Report: Extensive Phosphorylation of Interleukin-1 Receptor-Associated Kinase 4 in a Patient With Schnitzler Syndrome - Hodl, Isabel; Bosch, Philipp; Dreo, Barbara; Stradner, Martin H. (Frontiers in Immunology, 2020)
Schnitzler syndrome (SchS) is a rare autoinflammatory disease, characterized by urticarial rash, recurrent fever, osteo-articular pain/arthritis with bone condensation and monoclonal gammopathy. Diagnosis may be difficult due to overlapping signs with other diseases. Here, we describe the case of a 62-year-old man with SchS, who was initially misdiagnosed with multicentric Castleman disease (MCD). As excessive release of IL-6 is characteristic of MCD, in contrast to IL-1 in SchS, we measured the phosphorylation of intracellular signaling proteins of the respective pathways by flow cytometry. We found a distinct increase of phosphorylated IRAK-4 in our patient’s B cells and monocytes while phosphorylation of STAT-3 was low, suggesting predominant IL-1 signaling. In accordance with these results and the classification criteria, we established the diagnosis of SchS instead of MCD and commenced therapy with the IL-1 receptor antagonist anakinra. We observed a rapid remission of signs accompanied by a reduction of phosphorylated IRAK-4 to normal levels. In conclusion, we propose phosphorylated IRAK-4 in B cells and monocytes as a potential marker for diagnosis of Schnitzler syndrome and for treatment response to IL-1 blockade.